2014
DOI: 10.3109/13880209.2014.914231
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil ofPsidium cattleianumleaves: Antioxidant and antifungal activity

Abstract: Context: Psidium cattleianum Sabine (Myrtacea) is rich in vitamin C and phenolic compounds, including epicatechin and gallic acid as the main components. Objective: To evaluate the antifungal and antioxidant capacity in vitro of the essential oil of araçá (EOA). The acute toxicity of the EOA also was evaluated in mice. Materials and methods: The leaves of the P. cattleianum were extracted by steam distillation. The antioxidant capacity was evaluated by in vitro tests [1,1-diphenyl-2-picryl-hydrazyl (DPPH), 2,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 39 publications
0
16
2
4
Order By: Relevance
“…(2016b) observed fluconazole and all extracts had high inhibitor concentrations, however, when these were in association with sub-inhibitory concentrations (MIC/16), fluconazole had an improved effect, thus a synergistic effect was observed in the combination of fluconazole with extracts of Psidium brownianum against all strains of Candida ( Morais-Braga et al, 2016b ). According to this study, Castro et al (2015) demonstrated that the P. cattleianum essential oil had an effect on the inhibition of important clinical fungal strains such as Trichosporon asahii ( Castro et al, 2015 ), C. parapsilosis , C. albicans , C. lipolytica and C. guilhermondi , with concentrations ranging from 41.67 ± 18.04 to 16,670 ± 72.17 µg/mL for the tested strains.…”
Section: Discussionmentioning
confidence: 93%
“…(2016b) observed fluconazole and all extracts had high inhibitor concentrations, however, when these were in association with sub-inhibitory concentrations (MIC/16), fluconazole had an improved effect, thus a synergistic effect was observed in the combination of fluconazole with extracts of Psidium brownianum against all strains of Candida ( Morais-Braga et al, 2016b ). According to this study, Castro et al (2015) demonstrated that the P. cattleianum essential oil had an effect on the inhibition of important clinical fungal strains such as Trichosporon asahii ( Castro et al, 2015 ), C. parapsilosis , C. albicans , C. lipolytica and C. guilhermondi , with concentrations ranging from 41.67 ± 18.04 to 16,670 ± 72.17 µg/mL for the tested strains.…”
Section: Discussionmentioning
confidence: 93%
“…A concentração de 0,1% não apresentou inibição significativa (FIGURA 2). Em estudos anteriores, foi possível verificar que os óleos essenciais de E. uniflora e P. cattleianum demonstraram atividade antifúngica (CASTRO et al, 2015). Santos (2016) comparou os óleos essenciais de cinco espécies da família Myrtaceae (Pitanga, Goiaba, Grumixama, Jamelão e Araçá) para atividade antifúngica, utilizando o fungo patógeno Fusarium oxysporum.…”
Section: Resultados E Discussõesunclassified
“…Pode-se observar que a AA% dos extratos etanólico e de acetato de etila em ambas as espécies vegetais foi maior, onde houve aumento nesta atividade de acordo com o aumento da concentração do extrato analisado, sendo que na maior concentração analisada de 50 µg/mL o extrato (Braga et al, 2014;Castro et al, 2014;Fernandes et al, 2014;Moreno et al, 2014;Seo et al, 2014;Thakur & Arya, 2014).…”
Section: Resultsunclassified